2003
DOI: 10.1016/s0278-6915(03)00173-x
|View full text |Cite
|
Sign up to set email alerts
|

Black bean (Phaseolus vulgaris L.) as a protective agent against DNA damage in mice

Abstract: This study was designed to evaluate the toxicogenetic or protective effect of cooked and dehydrated black beans (Phaseolus vulgaris L.) in bone marrow and peripheral blood cells of exposed mice. The frequency of micronuclei detected using the bone marrow erythrocyte micronucleus test and level of DNA lesions detected by the comet assay were chosen as end-points reflecting mutagenic and genotoxic damage, respectively. Initially, Swiss male mice were fed with a 20% black bean diet in order to detect mutagenic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 19 publications
3
53
1
5
Order By: Relevance
“…Kumar et al (2003) reported that TI activity from defatted soy flour ranged from 42 to 113 mg g −1 and location effects on TI activity were nonsignificant. The potential health benefit of common bean is attributed to the presence of secondary metabolites such as phenolic compounds that possess antioxidant properties (Azevedo et al 2003). The content of total phenols, flavonols and ortho-dihydroxy phenols in different genotypes ranged from 1.0-1.5, 0.20-0.34 and 0.10-0.21 mg g −1 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Kumar et al (2003) reported that TI activity from defatted soy flour ranged from 42 to 113 mg g −1 and location effects on TI activity were nonsignificant. The potential health benefit of common bean is attributed to the presence of secondary metabolites such as phenolic compounds that possess antioxidant properties (Azevedo et al 2003). The content of total phenols, flavonols and ortho-dihydroxy phenols in different genotypes ranged from 1.0-1.5, 0.20-0.34 and 0.10-0.21 mg g −1 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, colored dry beans possess strong in vitro antioxidant activity (Beninger and Hosfield 2003;Madhujith and Shahidi 2005) which may explain the protective benefits of bean consumption on development of degenerative diseases. High in soluble fibre, protein and low in fat bean consumption has been inversely associated with reduced risk of coronary diseases and some types of cancer (Azevedo et al 2003;Winham and Hutchins 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Dry legumes are a good source of bioactive polyphenols [4] and also contribute to polyphenol intake from other foods [5]. The antioxidant capacity [6] and the antimutagenic [7][8][9][10], apoptosis-related [11] and antiproliferative effects of legumes are associated with the presence of phenolic compounds [12,13]. The abundance of phenolic compounds in such legumes as the common bean (Phaseolus vulgaris) [9], faba (broad) bean (Vicia faba) [14,15], beach pea (Lathyrus maritimus) [16], Total Phenolic Content and Antioxidant Activity of Chickpea (Cicer arietinum L.) as Affected 725 by Soaking and Cooking Conditions mung bean (Vigna radiata) [17], lentil (Lens culinaris) [18] and chickpea (Cicer arietinum) [19][20][21][22] implies that they may be significant food sources of active antioxidants.…”
Section: Introductionmentioning
confidence: 99%